Comparison of chemotherapeutic agents as a myeloablative conditioning with total body irradiation for pediatric acute lymphoblastic leukemia: A study from the pediatric ALL working group of the Japan Society for Hematopoietic Cell Transplantation. Issue 10 (5th June 2015) - Kato, Motohiro; Ishida, Hiroyuki; Koh, Katsuyoshi; Inagaki, Jiro; Kato, Keisuke; Goto, Hiroaki; Kaneko, Takashi; Cho, Yuko; Hashii, Yoshiko; Kurosawa, Hidemitsu; Takita, Junko; Hamamoto, Kazuko; et al.
<x xml:space="preserve">Abstract</x> Background As a partner of total body irradiation (TBI) in hematopoietic stem cell transplantation (HSCT) for pediatric acute lymphoblastic leukemia (ALL), various cytotoxic agents are used, but the optimal combination is still unclear. Procedure We retrospectively analyzed 767 children who received TBI‐based myeloablative allogeneic HSCT in complete remission (CR), using nationwide registry data of the Japan Society for Hematopoietic Cell Transplantation. Combinations of chemotherapy were categorized as follows: cyclophosphamide (CY) (n = 74), melphalan (L‐PAM) (n = 139), CY + etoposide (VP16) (n = 408), CY + cytarabine (AraC) (n = 73), and others (n = 73). Results Event‐free survival (EFS) at 5 years after HSCT was 62.2% for CY, 71.4% for L‐PAM, 67.6% for CY + VP16, 52.6% for CY + AraC, and 59.1% for others (P = 0.009). Further detailed comparison of LPAM and CY + VP16 demonstrated superior EFS for LPAM (83.2 ± 6.7%), with a marked difference compared with CY + VP16 (66.7 ± 4.9%) when limited to HSCT from a matched related donor (MRD), and this result was reproduced regardless of disease status (CR1 or CR2). However, EFS for CY + VP16 (68.3 ± 2.8%) was comparable to that for LPAM (64.5 ± 5.7%, P = 0.37) in HSCT from alternative donors, because higher non‐relapse mortality attenuated the advantage of LPAM. Conclusions For pediatric ALL in remission, LPAM could provide superior EFS for HSCT from MRD; however, compared to LPAM, CY + VP16 has similar EFS for HSCT from an alternative donor. Pediatr Blood Cancer 2015;62:1844–1850. © 2015 Wiley Periodicals, Inc.